Role of Sonic hedgehog signaling in cell cycle, oxidative stress, and autophagy of temozolomide resistant glioblastoma - Honorato, Jessica R. (2020)
Acesso aberto em 27/08;/2020 - https://onlinelibrary.wiley.com/doi/abs/10.1002/jcp.29274